Unilateral recanalisation of hypogastric artery after ligation for postpartum haemorrhage treatment - Raba, Grzegorz (Termedia Publishing House, 2013)
Internal iliac artery ligation has been a valued method of treating postpartum haemorrhage saving women's fertility. It is considered as an irreversible procedure with no possibility of recanalisation. The manuscript concerns a case of unilateral recanalisation of the hypogastric artery after ligation as a method of postpartum haemorrhage treatment. Material: 24 year old woman with body mass index 28 kg/m(2) with ligated internal iliac arteries due to postpartum haemorrhage. In the place of surgical ligation, the partial recanalisation of the internal iliac artery was noticed. Five mm under the narrowing there was found the telectasis of vessel's diameter with turbulent blood flow and contrast back. There can occur partial recanalization in the ligated internal iliac artery after obliteration in postpartum haemorrhage treatment. Exfoliation of endothelium shows that the process of recanalisation may be a risk factor of further complications of internal iliac artery ligation.